Elementary Students' Independence in Solving Mathematics Learning Problems in Post COVID-19 Pandemic - Sundari Sundari; Djalal Fuadi; Yulia Maftuhah Hidayati; Laili Etika Rahmawati; Endang Fauziati; Sutama Sutama (STAI Hubbulwathan Duri, 2022)
Independent learning is one of the important aspects of solving Mathematics learning problems. The novelty of this research is the independence of students in solving mathematics learning problems in elementary schools during post-pandemic era. The purpose of this study is to describe the elementary students' independence in solving Mathematics learning problems in the post-COVID-19 pandemic. This research approach is qualitative with a case study design. The research was conducted in sixth-grade students of SDN 01 Papahan Karanganyar. Data collection used interviews, observation, and documentation techniques. The researcher tested validity data with technical and source triangulation. The data analysis used interactive analysis techniques, namely data collection, reduction, presentation, and conclusions. The results showed that most of the students were able to solve mathematical problems in the post-COVID-19 pandemic independently, marked by: 74.07% of students can understand their problems, 92.59% of students could plan their problem solving, 77.78% of students could solve their problems correctly and systematically, and 77.78% of students could re-check the results of solving their problems. The research implies that students who can solve mathematical problems independently will use the knowledge, skills, and experience gained to achieve optimal learning outcomes and use their mindset to solve problems in everyday life without relying on the help of others.